2019
DOI: 10.1002/mrd.23268
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term heat stress impairs testicular functions in the American oyster, Crassostrea virginica: Molecular mechanisms and induction of oxidative stress and apoptosis in spermatogenic cells

Abstract: Global temperature is increasing due to anthropogenic activities. Abnormal temperature has devastating effects on growth, reproduction, and development of aquatic organisms. In this study, we examined the effects of short-term exposure to elevated temperatures (28 and 32°C for 1 week) on testicular functions, heat shock protein-70 (HSP70), dinitrophenyl protein (DNP, a biomarker of reactive oxygen species [ROS]), and nitrotyrosine protein (NTP, an indicator of reactive nitrogen species [RNS]) expressions, prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 74 publications
(123 reference statements)
3
19
0
Order By: Relevance
“…Recent studies on the European flat oyster, Ostrea edulis, and on the eastern oyster, Crassostrea virginica, showed the direct effect of temperature on sperm production [55], gametogenesis, and sex ratio through the role of steroid hormones [56]. In fact, a correlation was found between estradiol and testosterone determined in developing gonads.…”
Section: Molluscamentioning
confidence: 99%
“…Recent studies on the European flat oyster, Ostrea edulis, and on the eastern oyster, Crassostrea virginica, showed the direct effect of temperature on sperm production [55], gametogenesis, and sex ratio through the role of steroid hormones [56]. In fact, a correlation was found between estradiol and testosterone determined in developing gonads.…”
Section: Molluscamentioning
confidence: 99%
“…In male animals, HS reduces sperm production and increases the number of deformed sperm by damaging testicular tissue [2]. Previous studies have shown that the degree of testicular injury is positively correlated to the decrease in reproductive performance caused by HS in male animals [3]. Although heat-induced testicular injury has previously been investigated, additional studies are required to fully understand the mechanism by which HS impairs the normal physiological function of the testicles and to explore more effective and economical therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported the use of antioxidants to protect the testis against the adverse effects of HS [14]. Moreover, oxidative stress and ER stress have been shown to play important roles in testicular damage caused by hyperthermia [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, oxidative stress could result in cell cycle arrest and trigger apoptosis, and plays an essential role during the process of spermatogenesis (Xu et al, 2019). A growing body of evidence demonstrates that Bax, Bcl‐2 and Caspase family plays a pivotal role in eliminating defective germ cells during spermatogenesis (Nash & Rahman, 2019; Print & Loveland, 2000). Furthermore, recent studies have demonstrated that caspase 9 and the executioner caspases 3, 6, and 7 involve apoptosis and abnormal spermatogenesis (McComb et al, 2019; Sinha Hikim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HS response due to elevated temperatures involved in the activation of the transcription factor, such as the production of hypoxia-inducible factor-1 (HIF-1; Baird, Turnbull, & Johnson, 2006), reactive oxygen species (ROS) and free radicals, accompanied by lipid peroxidation, glutathione (GSH), and superoxide dismutase (SOD) changes in the oxidation index. Interestingly, spermatozoa are highly sensitive to ROS-induced damage, overproduction of ROS can be detrimental to sperm and may lead to male infertility (Nash & Rahman, 2019). A recent report by Park et al (2017) indicated that capsaicin may attenuate spermatogenic cell death induced by scrotal hyperthermia through its anti-oxidative (levels of MDA, PHGPx, and Hsp72) and anti-apoptotic (levels of TUNEL-positive cells, and Bcl-xL and Bax) activities.…”
Section: Introductionmentioning
confidence: 99%